Minimum Error Entropy Filter for Fault Detection of Networked Control Systems - Guolian Hou; Mifeng Ren; Lilong Du; Jianhua Zhang (Entropy, 2012)
In this paper, fault detection of networked control systems with random delays, packet dropout and noises is studied. The filter is designed using a minimum error entropy criterion. The residual generated by the filter is then evaluated to detect faults in networked control systems. An illustrative networked control system is used to verify the effectiveness of the proposed approach.